Etiology and treatment of mouth breathing habit - Ardiansyah S. Pawinru (Makassar Dental Journal PDGI Makassar, 2020)
Malocclusion is a condition that deviates from normal occlusion including irregularities of the teeth in the arch of the jaw such as crowding, protrusive, malposition and relationships that are not harmonious with the antagonist teeth. Non-physiological oral habits are abnormal human habits that cause stresses and tendencies that persist and are repeated continuously so that it affects craniofacial growth and is usually called bad habits. Changes in the activity of these muscles will lead to modification of facial growth patterns and head posture that can result in dentofacial deformity. Adaptation from nasal breathing to mouth breathing causes several unhealthy things, such as chronic middle ear infections, sinusitis, upper respiratory tract infections, sleep disor-ders, and facial growth disorders.